2012
DOI: 10.3892/ijo.2012.1490
|View full text |Cite
|
Sign up to set email alerts
|

The role of human peritoneal mesothelial cells in the fibrosis and progression of gastric cancer

Abstract: Peritoneal dissemination is the most frequent metastatic pattern of scirrhous gastric cancer. However, despite extensive research effort, disease outcomes have not improved sufficiently. Tumor progression and metastasis result from interactions between cancer and various cells in the stroma, including endothelial cells, immune cells and fibroblasts. Fibroblasts have been particularly well studied; they are known to change into carcinoma-associated fibroblasts (CAFs) and produce transforming growth factor β (TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 33 publications
2
63
0
Order By: Relevance
“…These results indicated that CAFs have a crucial role in the growth and invasion of gastric cancer cells (58). Another previous study verified that HPMCs are one source of CAFs (25). HPMCs have a spindle-shaped morphology following the stimulation of TGF-β and these activated HPMCs are more invasive.…”
Section: Promotion Of Metastasis By Cafmentioning
confidence: 58%
See 2 more Smart Citations
“…These results indicated that CAFs have a crucial role in the growth and invasion of gastric cancer cells (58). Another previous study verified that HPMCs are one source of CAFs (25). HPMCs have a spindle-shaped morphology following the stimulation of TGF-β and these activated HPMCs are more invasive.…”
Section: Promotion Of Metastasis By Cafmentioning
confidence: 58%
“…Taken together, CAFs in gastric cancer originate from orthotopic fibroblasts, HPMCs and bone marrow-derived cells, and they promote the progression of gastric cancer in a number of ways (25,58,60). The CXCL12/CXCR4 axis may be required in the migration of CAFs.…”
Section: Promotion Of Metastasis By Cafmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, bone marrow-derived mesenchymal stem cells, hematopoietic stem cells, epithelial cells that undergo the EMT, and endothelial cells that undergo the endothelial-mesenchymal transition are considered possible predecessors of CAFs (Figure 2). In gastric cancer, human peritoneal mesothelial cells (HPMCs) transform into myofibroblast-like cells following exposure to TGF-β, and these cells contribute to stromal fibrosis in a mouse xenograft model when coinoculated with MKN45 gastric cancer cells [66]. Moreover, in vivo experiment demonstrate that bone marrow-derived cells (fibrocytes) migrate and enhance tumor proliferation and fibrosis via the SDF-1/CXCR4 system [67].…”
Section: Cancer-associated Fibroblasts (Cafs) In the Microenvironmentmentioning
confidence: 99%
“…Although myofibroblasts have been reported to derive from resident peritoneal fibroblasts, human peritoneal mesothelial cells (hPMCs) (16,17), bone marrow progenitor cells or the primary tumor itself (18,19), the origin of these myofibroblasts has not been clearly established. Also, during the initial stages of peritoneal (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%